Determinación de Anticuerpos para Virus de Inmunodeficiencia Felina y Leucemia Felina en Jaguares (panthera onca) y Pumas (puma concolor) de los medios de Conservación ex situ del Ecuador por medio de la Técnica de Inmunocromatografía. - Chico Frías, Marco Antonio (2019)
Feline Immunodeficiency Virus (FIV) and Feline Leukemia Virus (FeLV) are important in domestic cats; these affect these individuals greatly. Several studies show that big felines such as, lions (Panthera leo) in Africa, and pumas (Puma concolor corvi) in North America have also been infected with these viruses. This represents a potential risk for the worldwide population of big cats. This study aims to detect the presence of FIV and FeLV in endemic Ecuadorian felines Puma concolor and Panthera onca that live in captivity in seven different zoos around the country. During the experimental phase, 28 blood samples were taken; these were analyzed with an Immunochromatography test, SNAP COMBO FeLV Ag/FIV Ak (IDEXX)®. The 100% seronegative for both viruses imply that big endemic felines did not have direct contact with domestic cats. However, further studies should be conducted in order to fully discard the presence of FIV and FeLV in these individuals. Medical records for each individual of the study were also created, so to standardize how data should be collected. This was essential also to document relevant information related to contagious diseases that these protected species can be exposed. Interviews to zookeepers were also applied with the purpose of understanding possible factors for these animals to get infected with FIV and FeLV. The physical evaluation of the enclosures of the 28 individuals determined that their design respond to the animal size, hazard, and charisma but not to biosecurity. These both data gathering tools evidence the lack of specific protocols to handle big cats, as well as, precarious preventive medicine applications in all zoos. The information collected in this study evaluated a historically forgotten area of wildlife veterinary medicine, the research on risk factors for vulnerable species.